2015
DOI: 10.11604/pamj.2015.21.28.5195
|View full text |Cite
|
Sign up to set email alerts
|

Delayed initiation of anti-retroviral therapy in TB/HIV co-infected patients, Sanyati District, Zimbabwe, 2011-2012

Abstract: IntroductionTuberculosis (TB) remains a public health problem and is driven by HIV. Recent studies indicate that anti-retroviral therapy (ART) initiated during the first two months of anti-TB treatment (ATT) reduces risk of HIV morbidity and mortality. In Sanyati district, 14% of TB/HIV co-infected patients were initiated on ART during TB treatment, in 2010. The study was conducted to determine the magnitude and determinants of delay in ART initiation, in TB/HIV co-infected patients.MethodsAn analytic cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…However, not much attention has been given to prevent DP for the vulnerable groups particularly Tb/HIV co-infected patients which remains one of the vastest defies in the reduction of HIV infection in resource scare countries including Ethiopia. Nearly 60 % of the patients in our study were delayed presenters, a finding that is similar with a study conducted in Zimbabwe [38]. This is also a comparable magnitude with DP of general HIV population in Africa [22, 26].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, not much attention has been given to prevent DP for the vulnerable groups particularly Tb/HIV co-infected patients which remains one of the vastest defies in the reduction of HIV infection in resource scare countries including Ethiopia. Nearly 60 % of the patients in our study were delayed presenters, a finding that is similar with a study conducted in Zimbabwe [38]. This is also a comparable magnitude with DP of general HIV population in Africa [22, 26].…”
Section: Discussionsupporting
confidence: 90%
“…Findings of a previous study conducted in Zimbabwe [38] depicted that being treated for Tb first time, staying more than 5 km from a clinic, and having a family member on ART were factors for delayed ART initiation. In addition, findings of another study from Malawi [47] revealed that cost of transport to the hospital ART site was significantly associated with ART acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies looking at spatial heterogeneity of viral suppression in this province reported similar results [8,25]. People in this province are likely to present late for health care [26], delay ART initiation [27] or engage in sexual activities with multiple partners which subsequently compromise viral suppression among HIV patients [28,29]. Therefore, interventions such as self-testing [30], pre-exposure prophylaxis (PrEP) pills for high-risk groups [31] should be intensified in such regions.…”
Section: Discussionmentioning
confidence: 65%
“…A possible explanation to this observation is that those who die in the first few weeks of treatment report to the hospitals late. The causes of delay may be due to fear of drug toxicities, stigmatisation, self-medication, delay in diagnosis of TB and/or HIV infection and counselling among other others [8, 29].…”
Section: Discussionmentioning
confidence: 99%